Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/cbf.3634
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms driving the initiation and direction of endothelial sprouting in organotypic co‐culture of aorta and spinal cord tissues

Abstract: The resumption of blood supply in spinal cord (SC) after injury is a prerequisite of its recovery. To expose the mechanisms of damaged SC revascularization we have used an organotypic SC/aortic fragments (AF) co‐culture where, as we showed previously, damaged SC tissue induces AF cell sprouting but repels them away. Supplementation of culture medium with exogenous VEGF‐A165 redirects the migrating aortic endothelial cells towards SC tissue. This effect and the pattern of sFlt1 expression (a soluble form of VEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…According to a recent study involving aorta and spinal cord tissue co-cultures, OPN was identified as one of the proangiogenic factors (Endostatin/Collagen18) that revived the migration/proliferation of CD31+ and αSMA+ aortic cells in neuronal culture medium. Moreover, it was produced by both spinal cord tissue and aortic fragments 39 . For the first time, our study confirms OPN’s proangiogenic role after SCI in animal models, as evidenced by the revocation of CD31 immunofluorescent signal enhancement after SCI in OPN knockdown mice.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…According to a recent study involving aorta and spinal cord tissue co-cultures, OPN was identified as one of the proangiogenic factors (Endostatin/Collagen18) that revived the migration/proliferation of CD31+ and αSMA+ aortic cells in neuronal culture medium. Moreover, it was produced by both spinal cord tissue and aortic fragments 39 . For the first time, our study confirms OPN’s proangiogenic role after SCI in animal models, as evidenced by the revocation of CD31 immunofluorescent signal enhancement after SCI in OPN knockdown mice.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, it was produced by both spinal cord tissue and aortic fragments. 39 For the first time, our study confirms OPN's proangiogenic role after SCI in animal models, as evidenced by the revocation of CD31 immunofluorescent signal enhancement after SCI in OPN knockdown mice. OPN could promote angiogenesis through VEGF and/or AKT pathways, 40,41 as we detected potential modulation of VEGF and AKT phosphorylation mediated by OPN post-SCI in this study.…”
Section: Discussionsupporting
confidence: 73%